Effects of blade parameters on the hydrodynamic performance of an impulse turbine of oscillation water column wave energy. (15th March 2021) - Wang, Xiu; Yan, Yan; Wang, Wen-Quan
Abstract: The impulse turbine is one of the most important devices of oscillating water column wave energy. The air through the rotor blades passage drives the rotor rotating and does work. Thus, reasonable rotor blade parameters directly determine the performance of the impulse turbine. This paper uses a computational fluid dynamics technique to analyze the influence of three rotor blade parameters, including rotor blade thickness, rotor blade rotation angle, and rotor blade incident angle on the efficiency of impulse turbine. The results show that the blade thickness is insensitive to the efficiency although the torque coefficient increases with the rising of thickness. The efficiency of the turbine increases with the decrease of the rotation angle or the increase of the incident angle. The efficient peak value of 57% is achieved at W = 16.1 mm, α = − 6 °, and λ = 30 ° at the flow coefficient of 1.0. Changing the structural parameters of the blade can not only change the pressure distribution of the blade, but also affect the velocity distribution and vortex formed. The energy loss is mainly attributed that the impulse loss at the initial segment and the energy dissipation at the trailing edge wake fields of the blade and downstream guide vane. Highlights: Effects of blade thickness, rotation angle and incident angle on efficient were discussed. Major reasons of leading to energy loss were investigated. The efficient peak value of 57% is achieved.